ANALISIS PENGARUH PENAMBAHAN ABU AMPAS TEBU SEBAGAI FILLER PADA CAMPURAN ASPAL AC-BC - Rosyad, Farlin; Salsabila, Ranti (Ensiklopedia of Journal, 2024)
Asphalt is a thick liquid which is a hydrocarbon compound with small amounts of sulfur, oxygen and chlorine. Asphalt as a binding material for flexible pavement has viscoelastic properties, a combination of elastic and viscous properties. Asphalt is obtained from petroleum through a refining process or contained in natural materials as part of natural materials found with other materials. In an effort to add substitutes for fine materials that can be used as ingredients in asphalt mixtures, sugarcane bagasse ash, which is easily obtained, was used in research as an alternative fine material in asphalt mixtures. The asphalt used in this research is conventional 60/70 asphalt originating from PT. Perdana Perdana Abadi Perkasa. The aim of this research is to determine the effect of using bagasse ash as a filler in the Asphalt Concret-Binder Course (AC-BC) mixture. Based on the Marshall parameter test results, in terms of variations in the density value of the mixture, in terms of variations in fineness, it tends to increase, the density value of the normal mixture is 2,287gr, then the density value for each variation in fineness of 0.5% is a maximum of 2,292gr, the maximum density value is 1. % is 2,295gr, the maximum density value at 1.5% is 2,296gr and the maximum density value at 2% is 2,299gr, the maximum density value at 2.5% is 2,315gr, the maximum density value at 3% is 2,318gr.Keyword : Bagasse ash, conventional asphalt, AC-BC, density, stability